KAJIAN PENGAMBILAN KEPUTUSAN MAHASISWA ATAS PEMILIHAN STUDI PADA PROGRAM STUDI MBI JURUSAN ADM NIAGA POLITEKNIK NEGERI SEMARANG - Haribowo, Putut - (Politeknik Negeri Semarang, 2015)
The aim of the research to identify thecharacter of students internal customer, toanalyse the factor which influence thestudent’s decision in choosing to study atProdi Manajemen Bisnis Internasioal JurusanAdministrasi Niaga Politeknik NegeriSemarang. And to analyse the factor whichthe most dominant in influencing on student’sdecision. To collect data by using questionairand analyzed by descriptive analysis methodand multiple regression analysis.The result of this research, indicate R=0,854means dependent variable and independentvariable has correlation. F test is significantand Adjusted R2=0,705 indicate that 70,5%variation dependent variable was influencedby the fourth independent variable.Partially the result of regression analysisindicate that coefficient factor culturalvariable b=0,064, sig=0,454 it meanscultural factor variable is not significant.Social factor variable, b=0,418, sig=0,009,Personal factor variable b=0,247, sig=0,018and Phycology factor variable b=0,235,sig=0,045 positive influence to chosendecision factor significantly.